EFEK MEDAN ELEKTROMAGNET PADA MESIN BENSIN TERHADAP EMISI GAS BUANG DAN ENERGI PEMBAKARAN - Tatun H Nufus; Andi Ulfiana; Isnanda Nuriskasari; Sri Lestari (P3M Politeknik Negeri Indramayu, 2021)
The purpose of this study was to analyze the effects of electromagnetic fields on combustion quality, especially on gasoline engines. One of the indicators of good combustion quality was environmentally friendly exhaust emissions and relatively large combustion energy. This research uses an experimental method, with the independent variables magnetic field strength and fuel. The field strength used in this study consisted of 4 variations, namely 647 Gauss, 847 Gauss, 1068 Gauss and 1419 gauss, while the fuel used was E0 (premium 100% bioethanol 0%), E10 (premium 90% bioethanol 10%), E20 (premium 80% bioethanol 20%), and E30. (premium 70% bioethanol 30%). The parameters of the electromagnetic field strength and various types of fuel composition were used to test exhaust gas emissions and combustion energy (as the dependent variable) on the 125cc MIO gasoline motorbike in 2018.The result was that the levels of CO2 exhaust emissions increased by 35% and CO levels decreased by 71%, combustion energy increases in the range of 13-21%. The greater the electromagnetic field provided, the more environmentally friendly the exhaust emissions are and the greater the combustion energy.